2018
DOI: 10.3329/ijarit.v8i2.40553
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ acceptance of insects as an alternative protein source in poultry feeds

Abstract: The research aimed at assessing the perceptions and willingness of poultry farmers, feed traders and processors to use insects as a source of protein ingredient in poultry feed. The research used a cross-sectional design and a structured questionnaire to collect quantitative data from 287 poultry farmers and 71 feed traders from 3 culturally diverse regions in Uganda. The study findings revealed that majority of the farmers mixed their own poultry feed. Willingness to use insects in poultry feeds was expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…High literacy levels facilitate the search, access and comprehension of new and existing information. Educated farmers perceive market research as a critical component to safeguard against economic losses experienced during distress sales [54].…”
Section: Discussionmentioning
confidence: 99%
“…High literacy levels facilitate the search, access and comprehension of new and existing information. Educated farmers perceive market research as a critical component to safeguard against economic losses experienced during distress sales [54].…”
Section: Discussionmentioning
confidence: 99%
“…Edible insects are among the environmentally-friendly sources of proteins [ 85 ]. The adoption of insects as food or feed, if they can be produced in sustainable quantities, can increase consumer acceptance of insects as an alternative source of protein [ 86 ]; for instance, free-range chickens consume insects such as termites, grasshoppers, and many others. The integration of insects as poultry feed in commercial diets is still being adopted and this source of protein has not yet been fully integrated into commercial feeds [ 86 ].…”
Section: Consumers’ Attitude Towards the Use Of Insects As Food Or Feedmentioning
confidence: 99%
“…The adoption of insects as food or feed, if they can be produced in sustainable quantities, can increase consumer acceptance of insects as an alternative source of protein [ 86 ]; for instance, free-range chickens consume insects such as termites, grasshoppers, and many others. The integration of insects as poultry feed in commercial diets is still being adopted and this source of protein has not yet been fully integrated into commercial feeds [ 86 ]. Edible insects are being promoted as an alternative source of protein; however, the major challenge will be creating sustainable production systems that will safeguard the environment and ensure food safety and security [ 13 ].…”
Section: Consumers’ Attitude Towards the Use Of Insects As Food Or Feedmentioning
confidence: 99%
“…Several works of literature have proven that yellow mealworm has the potential to be used as an alternative source of protein in animal diets [12][13][14][15][16][17], although other insects such as cockroaches, termites, crickets, earthworms, grasshoppers and black soldier flies can be included in animal feeds [18][19][20][21][22][23]. Most of the insects are harvested from the wild using traditional methods which are unsustainable [24].…”
Section: Introductionmentioning
confidence: 99%
“…Consumers in Belgium were reported to be willing to accept the use of insects as poultry feeds [28]. In Uganda it was found that feed traders, processors and poultry farmers were willing to accept insects as an alternative source of protein in poultry diets [18]. In addition, insects such as grasshoppers, cockroaches, termites and white ants were most preferred by poultry farmers to rear and use for feeding poultry [18].…”
Section: Introductionmentioning
confidence: 99%